Australia 6 months after COVID-19 restrictions part 2: The impact of working from home. (November 2022) - Beck, Matthew J.; Hensher, David A.
Abstract: This paper (Part 2 in the paper series), building on earlier studies examining the Australian response, extends on findings related to travel activity, commuting, and attitudes towards COVID-19 measures (Part 1 in the paper series). In this paper we focus in detail on the impact of, and experiences with, working from home (WFH), perhaps the largest of the positive unintended consequence of the pandemic, with respect to transport, and a key lens through which the changing patterns in travel activity and attitudes discussed in Part 1 need to be understood. We conclude that through the widespread adoption of WFH as a result of nationwide public health orders, there is evidence emerging that WFH is now seen as an appealing instrument of change by employees and employers, there is growing support to continue to support WFH into the future. This represents a significant potential contribution to the future management of the transport network, especially in larger metropolitan areas. We also discuss policy implications of this result and what the international community may take from the Australian experience.